Estimated leaf area of yacon, Smallanthus sonchifolius (Poepp. & Endl.) H. Rob., through an indirect method. - Seminario-Cunya, Juan Francisco (2016)
The objective of this study was to estimate the leaf area of eight yacon morphotypes by simple linear regression analysis. The research was conducted between 2014 and 2015, in the Andean Roots and Tubers Program of the National University of Cajamarca, Peru (7° 10’ 00’’ S, 78° 30’00’’ W, 2650 masl). One hundred leaves of basal, middle and terminal strata of each morphotype in full bloom, were taken. The outlines of fresh leaves were drawn on paper and the blade’s length (L) and greater width (W), was measured. The measured blade’s area (or actual) was determined with digital planimeter. With the measured area (dependent variable) and the values of length, width, squared length, squared width, length x width and length/width (as independent variables), the regression analysis for each morphotype, was performed. In all morphotypes, except in two, the best equations to estimate the leaf area, were those in which intervened the product of L x W. The equation which allowed to estimate the leaf area of the morphotypes together was A= 20.41 + 0.4167 (L x W) (r2 = 0.89). Petiole area of the studied morphotypes represented 15% of the total leaf area.